1998
DOI: 10.1175/1520-0485(1998)028<1107:nawwaw>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Wind Waves and Wind Stress Fields from Voluntary Observing Ship Data

Abstract: On the basis of the collection of individual marine observations available from the Comprehensive OceanAtmosphere Data Set, major parameters of the sea state were evaluated. Climatological fields of wind waves and swell height and period, as well as significant wave height and resultant period are obtained for the North Atlantic Ocean for the period from 1964 to 1993. Validation of the results against instrumental records from National Data Buoy Center buoys and ocean weather station measurements indicate rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 62 publications
(36 reference statements)
5
63
1
1
Order By: Relevance
“…These data must be independently evaluated to produce good quality products. For example, North Atlantic and global wave climatologies (Gulev and Hasse, 1998;Gulev et al, 2003), and global distributions of total cloud cover and cloud-type amounts over the ocean have been derived (Warren et al, 1988) from ICOADS.…”
Section: Associated Products and Analysesmentioning
confidence: 99%
“…These data must be independently evaluated to produce good quality products. For example, North Atlantic and global wave climatologies (Gulev and Hasse, 1998;Gulev et al, 2003), and global distributions of total cloud cover and cloud-type amounts over the ocean have been derived (Warren et al, 1988) from ICOADS.…”
Section: Associated Products and Analysesmentioning
confidence: 99%
“…However, only 40-60% of the total number of reports includes wave information (Gulev and Hasse, 1998).…”
Section: O L U N Ta R Y O B S E R V I N G S H I P S P R O G R a Mmentioning
confidence: 99%
“…In the visual field, Laing (1985) compared shipreported wave heights with measurements and concluded that the reported data captured the physical characteristics of wave fields well and thus can be useful in climatological studies. Gulev and Hasse (1998) and Gulev et al (2003) derived North Atlantic (NA) and global wave climatology studies from ICOADS observations. Generally speaking, the accuracy of individual ship observations is not consistently high, but they remain an important source of gross information over oceans (e.g., Kent et al 2007).…”
Section: Introductionmentioning
confidence: 99%